THE EFFECT OF RECREATIONAL SPORT PARTICIPATION ON ACADEMIC MOTIVATION - Osman Gümüşgül; Ceren Gümüşgül (ümit doğan üstün, 2019)
The aim of this study was to investigate the effect of recreational sport participation on academic motivation. Totally, 144 students (108 male, 36 female) were taken part in this research. Data was gathered through Academic Motivation Scale which was developed by Vallerand et al. (1992) and translated to Turkish Language by Karagüven (2012). The scale has 28 items. In evaluation part for questionnaires answered by participants, Kolmogorov Smirnov normality test, T-Test and One Way ANOVA tests were applied. According to the results, it was statistically determined that there were significant differences on recreational participation, free time activity, recreational practising frequency and age (p<0,05); but there were not significant differences on analyses done for gender (p>0,05). Keywords: Recreational sports, free time activity, academic motivation